Child psychoanalytic psychotherapy: a single case study. Issue 1 (2nd January 2017) - Ramires, Vera Regina Röhnelt; Godinho, Lucia Belina Rech; Carvalho, Cibele; Gastaud, Marina; Goodman, Geoff
Abstract : Child psychoanalytic psychotherapy is a specific approach to the treatment of emotional, social and behavioural problems in children. There are hundreds of modalities of psychotherapy, and this continues to increase. The vast majority has not been investigated using controlled (or other types of) studies and not all of these methods are based on explicit etiological or therapeutic theories of change. A gap exists that should be filled between psychotherapeutic research and clinical practice. Based on these assumptions, the present study sought to analyse the first year of the psychotherapeutic process of a boy aged seven who was referred for psychotherapy. A descriptive study was performed, based on a single case study design. The participants were the child and his therapist and the main measure was the Child Psychotherapy Q-Set–CPQ, a procedure used to analyse the psychotherapeutic process in 3–13-year olds. The results show the main elements of the psychotherapy process, describing characteristics of the child, of the therapist and the dyad interaction.